Acessibilidade e políticas linguísticas educacionais para surdos: do contexto de produção textual às vivências na Universidade Federal do Maranhão - Dias, Walquiria Pereira da Silva (Universidade Federal de São Carlos, 2025)
Deaf communities have historically worked to promote greater social participation and the guarantee of rights. The presence of deaf people in various sectors of society is evident, creating a demand for interpretation and translation and, consequently, the need for professionals to ensure linguistic accessibility. The institutionalization of the Libras/Portuguese Language Translator and Interpreter (TILSP) has been a reflection of this situation, but it does not always meet the need for public policies that take deaf individuals into account as citizens who exercise their rights and duties using specific language modalities. In this sense, considering legal requirements and experiences within institutions, we investigate how public policies aimed at deaf people have been guided in the educational context, specifically in Higher Education. Thus, the general objective focuses on analyzing political convergences - of accessibility, educational and linguistic - that guide the education of deaf people at UFMA, taking as a starting point institutional documents and dialogues established with TILSPs working at the institution. The specific objectives are: a) To identify, in institutional documents, plans and/or actions that contemplate deaf people, seeking to understand the policies that guide the proposals, comparing them with reports about the practices; b) To problematize the implementation of policies (of accessibility, educational and linguistic) in the context of practice, with a view to devaluing the language and the subjects involved in the process; c) To rethink the context of practice, in order to mitigate proposals that are more consistent with the needs of deaf communities in Higher Education.Based on the debates on accessibility, originally conceived in the field of Special Education, we project the discussion to the arena of Language Policies, mobilizing the perspective of language as a linguistic right and not only as a communication resource. Considering the context of our analyses, Accessibility and Linguistic Policies are considered in dialogue with Educational Policies, taking into account the relationship between macro and micro contexts to think about Deaf Education. Methodologically, this is a qualitative approach, based on a case study, with the Federal University of Maranhão (UFMA) as the locus. Three stages were carried out: a) documentary research, in which, in addition to the general legislation that guides deaf education, we analyzed internal documents from UFMA; b) a focus group held with TILSPs working at UFMA, totaling three meetings; and c) an interview with the head of the Subsection of Libras Interpreters of the aforementioned institution, to complement data collected in the focus group. The data are analyzed considering the contexts and the value of practices in the implementation of official policies. We therefore consider that, between policies and experiences, there are knowledge and power relations that permeate the educational field and make translation and interpretation of/into sign languages an important part of a very complex mechanism. We hope that this study will contribute to the formulation of public policies in the field of Higher Education.

Las comunidades sordas han avanzado históricamente hacia una mayor participación social y la garantía de derechos. La presencia de personas sordas en diversos sectores de la sociedad es evidente, creando una demanda de interpretación y traducción y, en consecuencia, la necesidad de profesionales para lograr la accesibilidad lingüística. La institucionalización de la figura del traductor e intérprete de Libras/Lengua Portuguesa (TILSP) ha sido un reflejo de esta situación, pero no siempre atiende a la necesidad de políticas públicas que tengan en cuenta a los individuos sordos como ciudadanos que ejercen sus derechos y deberes a partir de lenguas de modalidades específicas. En esta dirección, considerando las determinaciones legales y las experiencias al interior de las instituciones, investigamos cómo las políticas públicas dirigidas a las personas sordas han sido orientadas en el contexto educativo, específicamente en la Educación Superior. Así, el objetivo general se centra en analizar las convergencias políticas - de accesibilidad, educativas y lingüísticas - que orientan la educación de las personas sordas en la UFMA, tomando como punto de partida documentos institucionales y diálogos establecidos con los TILSP que actúan en la institución. Los objetivos específicos son: a) Identificar, en los documentos institucionales, planes y/o acciones que incluyan a las personas sordas, buscando comprender las políticas que orientan las propuestas, comparándolas con los informes sobre las prácticas; b) Problematizar la implementación de políticas (de accesibilidad, educativas y lingüísticas) en el contexto de la práctica, con miras a desvalorizar/desvalorizar la lengua y los sujetos involucrados en el proceso; c) Re/pensar el contexto de la práctica, con el objetivo de mitigar propuestas más acordes a las necesidades de las comunidades sordas en la Educación Superior. A partir de los debates sobre accesibilidad, originalmente concebidos en el ámbito de la Educación Especial, proyectamos la discusión al ámbito de las Políticas Lingüísticas, movilizando la perspectiva de la lengua como un derecho lingüístico y no sólo como un recurso de comunicación. Considerando el contexto de nuestros análisis, la Accesibilidad y las Políticas Lingüísticas se piensan en diálogo con las Políticas Educativas, teniendo en cuenta la relación entre los contextos macro y micro para pensar la Educación de Sordos. Metodológicamente, se trata de un enfoque cualitativo, basado en un estudio de caso, teniendo como escenario la Universidad Federal de Maranhão (UFMA). Se completaron tres etapas: a) investigación documental, en la que, además de la legislación general que orienta la educación de los sordos, se analizaron documentos internos de la UFMA; b) grupo focal realizado con TILSP actuantes en la UFMA, totalizando tres reuniones; y c) entrevista con el jefe de la Subsección de Intérpretes de Libras de la mencionada institución, para complementar los datos recolectados en el grupo focal. Los datos se analizan considerando los contextos y el valor de las prácticas en la implementación de políticas oficiales. Consideramos pues que entre las políticas y las experiencias coexisten saberes y relaciones de poder que atraviesan el campo educativo y hacen de la traducción e interpretación de/hacia lenguas de señales una parte importante de un mecanismo muy complejo. Esperamos que este estudio contribuya a la formulación de políticas públicas en el campo de la Educación Superior.
Accessibility and educational linguistic policies for the deaf: from the context of text production to experiences at the Federal University of Maranhão
Accesibilidad y políticas linguísticas educativas para sordos: del contexto de producción textual a las vivencias en la Universidad Federal de Maranhão
Keywords: Educação Superior; Surdos; Políticas; Tradutores e intérpretes de Libras; Higher education; Deaf people; Policies; Libras translators and interpreters; Educación superior; Sordo; Políticas; Traductores e intérpretes de lengua de signos; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO